CONTROL OF THE ENVIRONMENTAL IMPACT OF URANIUM UNDERGROUND WELL MINING (ON THE EXAMPLE OF MYKHAILIVKA POLYGENIC DEPOSIT OF THE UKRAINIAN SHIELD) - Verkhovtsev, V.; Sushchuk К.; Tyshchenko, Yu.; Meshcheriakov, S.; Koliabina І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Nuclear energy is an important component of Ukraine’s national security. Providing this industry with its own raw materials is one of the priority, long-term tasks of the state. One of the ways to successfully solve this task is to create a favorable investment climate for the involvement of private business entities in the development of the domestic mining industry.In Ukraine, numerous uranium deposits have been explored, which are characterized by relatively small reserves, which is why until recently they were not considered promising for development by the state mining company Eastern Mining and Processing Plant (Zhovti Vody). These deposits are not profitable for development by traditional methods – mining or quarrying, but they can be worked out by the method of underground well leaching. In addition to lower capital costs, this method is also characterized by the fact that it is accompanied by a lower environmental load.The article highlights some aspects of the generalized results of the impact on the environment of the new activity analysis, which involves the creation of a private enterprise for research and industrial development and subsequent extraction of uranium at the Mykhailivka deposit in the Kazankivskyi district of the Mykolaiv region, which relate to the choice of technology evaluation for the extraction of minerals by the method of underground well leaching. The projected enterprise will consist of several temporary mining sites and a stationary industrial site of the processing complex, as well as engineering and transport infrastructure facilities. After working out the deposit, land reclamation and their return to land users and subsoil rehabilitation will be carried out, which will ensure their restoration to the pre-project state.On the territory that may be affected by the construction and operation of the planned enterprise, full-scale field and laboratory geo-ecological investigations were conducted and their results were described.